Twenty-Four-Hour Ambulatory Blood Pressure Monitoring - Camilo Pena-Hernandez; Kenneth Nugent; Meryem Tuncel (Journal of Primary Care & Community Health, 2020)
The diagnosis, management, and estimated mortality risk in patients with hypertension have been historically based on clinic or office blood pressure readings. Current evidence indicates that 24-hour ambulatory blood pressure monitoring should be an integral part of hypertension care. The 24-hour ambulatory monitors currently available on the market are small devices connected to the arm cuff with tubing that measure blood pressure every 15 to 30 minutes. After 24 hours, the patient returns, and the data are downloaded, including any information requested by the physician in a diary. The most useful information includes the 24-hour average blood pressure, the average daytime blood pressure, the average nighttime blood pressure, and the calculated percentage drop in blood pressure at night. The most widely used criteria for 24-hour measurements are from the American Heart Association 2017 guidelines and the European Society of Hypertension 2018 guidelines. Two important scenarios described in this document are white coat hypertension, in which patients have normal blood pressures at home but high blood pressures during office visits, and masked hypertension, in which patients are normotensive in the clinic but have high blood pressures outside of the office. The Centers for Medicare and Medicaid Services has made changes in its policy to allow reimbursement for a broader use of 24-hour ambulatory blood pressure monitoring within some specific guidelines. Primary care physicians should make more use of ambulatory blood pressure monitoring, especially in patients with difficult to manage hypertension.